4-Nitroquinoline-1-oxide-induced mutagen sensitivity and risk of cutaneous melanoma: a case–control analysis. Issue 2 (April 2016) - Wang, Li-E; Li, Chunying; Xiong, Ping; Gershenwald, Jeffrey E.; Prieto, Victor G.; Duvic, Madeleine; Lee, Jeffrey E.; Grimm, Elizabeth A.; Hsu, Tao C.; Wei, Qingyi
Abstract : Mutagen sensitivity assay, which measures the enhanced cellular response to DNA damage induced in vitro by mutagens/carcinogens, has been used in the study of cancer susceptibility. 4-Nitroquinoline-1-oxide (4-NQO), an ultraviolet (UV) radiation-mimetic chemical, can produce chromosomal breaks in mammalian cells and induce cancer. Given the potential role of 4-NQO as the experimental mutagen substituting for UV as the etiological carcinogen of cutaneous melanoma (CM), we tested the hypothesis that cellular sensitivity to 4-NQO is associated with the risk of developing CM in a case–control study of 133 patients with primary CM and 176 cancer-free controls. Short-term blood cultures were treated with 4-NQO at a final concentration of 10 μmol/l for 24 h and scored chromatid breaks in 50 well-spread metaphases. Multivariate logistic regression was used to calculate odds ratios and 95% confidence intervals. We found that the log-transformed frequency of chromatid breaks was significantly higher in 133 patients than in 176 controls ( P =0.004) and was associated with an increased risk for CM (adjusted odds ratio=1.78, 95% confidence interval: 1.12–2.84) after adjustment for age and sex. Moreover, as the chromatid break values increased, the risk for CM increased in a dose-dependent manner ( P trend =0.003). Further analysis explored a multiplicative interaction between the sensitivity to 4-NQO and a family history of skin cancer ( P interaction =0.004) on the risk of CM. Therefore, our findings suggest that sensitivity to 4-NQO may be a risk factor for the risk of CM, which is more sensitive than UV-induced chromotid breaks.